A ditadura militar no Brasil e a censura a obras de autoria de artistas mulheres engajadas (Ágora Journal, 2024)
The 20th century was marked by major world conflicts, such as World Wars I and II and the Cold War, which created fear in the world and resulted in a large number of injuries and deaths. Global bipolarization ended up affecting Latin America, which under the influence of the United States subjected many Cone Sur countries, including Brazil, to cruel and long-lasting dictatorial regimes. During this period, Brazil was strongly controlled by the armed forces, which persecuted the student movement, strike fronts, protests, and censored exhibitions and works of art. In a sociopolitical and cultural context dominated by men, women artists, even under various forms of repression, acted in an engaged way. Therefore, with this article we aim to analyze the performance of women artists and the adversities they faced during the Brazilian military dictatorship.Keywords: women artists; censorship; military dictatorship.
Keywords: women artists; censorship; military dictatorship; female engagement; conceptualism.